2015
DOI: 10.3390/fib3010041
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fiber-Reinforced Cements in Masonry Construction and Structural Rehabilitation

Abstract: Abstract:The use of fiber reinforcement in traditional concrete mixes has been extensively studied and has been slowly finding its regular use in practice. In contrast, opportunities for the use of fibers in masonry applications and structural rehabilitation projects (masonry and concrete structures) have not been as deeply investigated, where the base matrix may be a weaker cementitious mixture. This paper will summarize the findings of the author's research over the past 10 years in these particular applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 11 publications
2
15
0
1
Order By: Relevance
“…The nets have been also used in civil engineering field as a recycled fiber in order to reinforce or strengthen concrete, mortar and soil [5,6]. Even during the past three decades, the use of synthetic fiber, such as polyvinyl alcohol (PVA) fiber and polypropylene fiber has been paid attention, and it is successful in significantly improving mechanical properties, such as flexural strength, fracture toughness, and impact resistance, of fiber reinforced mortar and concrete [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, using of those fibers surely leads to higher energy consumption and emission for production process [6].…”
Section: Introductionmentioning
confidence: 99%
“…The nets have been also used in civil engineering field as a recycled fiber in order to reinforce or strengthen concrete, mortar and soil [5,6]. Even during the past three decades, the use of synthetic fiber, such as polyvinyl alcohol (PVA) fiber and polypropylene fiber has been paid attention, and it is successful in significantly improving mechanical properties, such as flexural strength, fracture toughness, and impact resistance, of fiber reinforced mortar and concrete [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, using of those fibers surely leads to higher energy consumption and emission for production process [6].…”
Section: Introductionmentioning
confidence: 99%
“…The plain concrete beams exhibit a very brittle behavior when subjected to fl exural loading whereas the polypropylene fi ber reinforced concrete beams show ductile failure. The research work carried out by Ece Erdogmous [13], concluded with recommendations that composition and strength of the initial cementations matrix as shown in both the masonry and the concrete structure application studies, the lower strength matrices may benefi t more from the fi ber addition compared to stronger base matrices. Flexural strength, toughness, energy absorption, and ductility of the FRM themselves are typically higher compared to the control mixture, even with lower fi ber percentages.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, application of surface plastering provides an additional 8% strength for masonry, compared with those of plain masonry. According to Erdogmus [20], the inclusion of fiber in the mortar increases the air content of the mix and due to this, the compressive strength of the mortar reduced. Here also, it is observed that the addition of coconut coir in the mix slightly reduced the compressive strength of masonry prisms.…”
Section: Pre-crack Behaviormentioning
confidence: 99%